Kajian Implementasi Tata Kelola Penganggaran Pembangunan Perumahan Akibat Bencana Gempa Bumi di Provinsi Nusa Tenggara Barat - Hariadi, Katuk Laksono (Fakultas Ekonomi dan Bisnis Universitas Samudra, 2025)
A series of major earthquakes in 2018 damaged 242,738 houses, killed 564 people, and triggered a massive need for rehabilitation and reconstruction, particularly in the housing sector in West Nusa Tenggara Province. The Indonesian government allocated Ready-to-Use Funds (DSP) through the National Disaster Management Agency (BNPB) to accelerate post-disaster response, but implementation faced various obstacles such as complex coordination between stakeholders, slow verification of aid recipient data, budget constraints, and the impact of the Covid-19 pandemic. This study highlights the disparity between budgeting policies and the realization of accelerated housing development in seven affected districts/cities. The study also shows that the dominance of APBN financing through DSP has resulted in dependence on the central government, with minimal contributions from APBD. These findings underscore the importance of reformulating post-disaster budget policies to be more responsive, flexible, and decentralized to accelerate the recovery process.